2020
DOI: 10.1103/physrevd.101.086022
|View full text |Cite
|
Sign up to set email alerts
|

Holographic computation of Wilson loops in a background with broken conformal invariance and finite chemical potential

Abstract: In this paper, we follow a 'bottom-up' AdS/QCD approach to holographically probe the dynamics of a moving qq pair inside a strongly coupled plasma at the boundary. We consider a deformed AdS-Reissner Nordström metric in the bulk in order to introduce nonconformality and finite quark density in the dual field theory. By boosting the gravity solution in a specific direction we consider two extreme cases of orientation, θ = 0, π/2, for the Wilson loop which in turn fixes the relative position of the qq pair with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The interaction between two quarks are reflected by the running coupling or the heavy quark -antiquark potential (free energy). In our previous study [81,92], we found that chemical potential and magnetic field will change the free energy of . Since the running coupling is extracted from the free energy of [7,103], we can infer that the chemical potential and magnetic field should have an influence on the running coupling.…”
Section: Discussionmentioning
confidence: 93%
“…The interaction between two quarks are reflected by the running coupling or the heavy quark -antiquark potential (free energy). In our previous study [81,92], we found that chemical potential and magnetic field will change the free energy of . Since the running coupling is extracted from the free energy of [7,103], we can infer that the chemical potential and magnetic field should have an influence on the running coupling.…”
Section: Discussionmentioning
confidence: 93%
“…by delving into the solution beyond the critical separation of the pair, which leads to the complex-valued string configurations, not the world-sheet thermal fluctuations method as we use here. In [52] the ImV Q Q of moving Q Q in a soft wall model with broken conformal invariance and finite chemical potential is discussed. As holographic examples, such as [49,[51][52][53] and [60] considered the moving cases, and they concluded that increasing rapidity leads to decreasing the dissociation length, implying the pair will be dissolved easier into a moving medium compared to the static medium, consistent with our findings here.…”
Section: Jhep03(2023)207mentioning
confidence: 99%
“…In [52] the ImV Q Q of moving Q Q in a soft wall model with broken conformal invariance and finite chemical potential is discussed. As holographic examples, such as [49,[51][52][53] and [60] considered the moving cases, and they concluded that increasing rapidity leads to decreasing the dissociation length, implying the pair will be dissolved easier into a moving medium compared to the static medium, consistent with our findings here. However, from EFT point of view, the reference [73] explored the in-medium modifications of heavy quarkonium states moving through a medium for two plausible situations:…”
Section: Jhep03(2023)207mentioning
confidence: 99%
“…Further, this quantity has been investigated in some nonconformal settings [24][25][26]. Other interesting results can be found in [27][28][29][30][31][32][33][34][35].…”
Section: Introduction Q Qmentioning
confidence: 99%